Quantitative microstructure characterization of Ag nanoparticle sintered joints for power die attachment - Wang, Yun; Li, Jianfeng; Agyakwa, Pearl; Johnson, Christopher Mark; Li, Shuguang (Taylor & Francis, 2014)
The samples of sintered Ag joints for power die attachments were prepared using paste of Ag nanoparticles at 240 °C and 5 MPa for 3 to 17 minutes. Their microstructural features were quantitatively characterized with scanning elec-tronic microscopy, transmission electron microscopy, X-ray diffraction and image analysis method. The resulting nor-malized thickness, pore size and porosity decreased, and grain size increased with increasing the sintering time. A time dependence of the form t1/n with n close to 2 or 3 can be further derived for the kinetics of the thinning, densification and grain growth within the sintered Ag joints.